2016
DOI: 10.1111/jnu.12254
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Symptom Distress Based on Gender and Palliative Care Designation Among Hospitalized Patients

Abstract: Purpose: To explore patient-reported symptom distress in relation to documentation of symptoms and palliative care designation in hospital inpatients. Design: This cross-sectional study analyzed data from 710 inpatients at two large hospitals in Sweden using the Edmonton Symptom Assessment Scale and the Memorial Symptom Assessment Scale. Chart reviews focused on nurses' and physicians' symptom documentation and palliative turning point. Methods: Descriptive statistics were calculated for all variables and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
(46 reference statements)
4
14
0
1
Order By: Relevance
“…Online Resources 4 and 5 indicated that tumor site and gender might be associated with patients' burden. In all, women had better POS scores but reported higher values for anxiety and fatigue than male patients which confirms results identified in other studies and underlines the need for a closer look at gender differences in future studies [28][29][30].…”
Section: Assessed For Eligibility (N=3155)supporting
confidence: 88%
“…Online Resources 4 and 5 indicated that tumor site and gender might be associated with patients' burden. In all, women had better POS scores but reported higher values for anxiety and fatigue than male patients which confirms results identified in other studies and underlines the need for a closer look at gender differences in future studies [28][29][30].…”
Section: Assessed For Eligibility (N=3155)supporting
confidence: 88%
“…Women also reported lower values on EQ VAS at both admission and discharge compared with men. These differences are supported by similar findings where women reported higher symptom distress than men, and where women had to report more symptoms for the caregivers to document those . In another study, women reported higher levels of distress from experienced symptoms than men did .…”
Section: Discussionsupporting
confidence: 52%
“…In der Forschung zur Palliativversorgung werden beispielsweise Diskrepanzen in der Selbsteinschätzung und im Berichten von Symptomen und Problemen zwischen Patient*innen beschrieben. Daher ist anzunehmen, dass Frauen und Männer folglich auch nicht die gleiche Behandlung und Symptomlinderung erhalten [6]. Es konnte auch gezeigt werden, dass Männer zögern, über ihren eigenen bevorstehenden Tod [7] sowie den Tod ihres/r Partner*in zu sprechen und dass sie durch den Verlust eines/r Ehepartners*in stärker betroffen sind als Frauen [8].…”
Section: Hintergrundunclassified